SPICE-Based Circuit Analysis of Power Flow Coupling Effect in Double-Input Cuk--Buck DC-DC Converters - Zhang, Hao; Gao, Jiao; Yi, Chuanzhi; Dong, Dachu; Zheng, Feng (IEEE transactions on power electronics, 2022)
An equivalent simulation program with integrated circuit emphasis (SPICE) based circuit is derived from the proposed small-signal averaged model of double-input Cuk--Buck dc-dc converter so that the power flow coupling effect amongst input/output ports is easy to be analyzed in terms of circuit theory rather than pure mathematics. Based on the equivalent SPICE-based circuit, common mode and differential mode power flow decomposition is presented to unveil the power flow coupling between three ports, and furthermore benefits frequency response analysis. It is shown that common mode perturbation analysis reveals the power flow coupling amongst input and output ports, whereas differential mode perturbation analysis does the power flow coupling between input ports. Meanwhile, the explanation of circuit knowledge is provided for power flow coupling effect. Particularly, it is found that the occurrence of the pseudo resonant phenomenon is the result of counteract effect of the common mode and differential mode components in power mismatched condition. Besides, the application of frequency-selective decoupling is proposed to weaken the power flow coupling between ports. Finally, theoretical analysis is verified by experimental ones. These results are useful to understand coupling effects in multiple-input converters and provide a guidance to the controller optimization and engineering application.